PENGARUH INDUSTRY-SPECIALIST AUDITOR DAN FAKTOR LAINNYA TERHADAP AUDIT REPORT LAG - MARSELLA DITTA; HERY GUNAWAN (E-Jurnal Manajemen Trisakti School of Management (TSM), 2026)
This study aims to provide empirical evidence on the influence on industry-specialist auditors and other factors on audit report lag. The research analyzes the effects of audit committee size, audit committee expertise, audit committee meetings, industry-specialist auditors, auditor reputation, firm size, profitability, and solvency on audit report lag. The object of this research is manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period. The sampling method used is purposive sampling, resulting in 109 manufacturing companies that meet the criteria, with a total of 327 data points utilized in the analysis. This study employs multiple regression analysis to examine the research variables. The findings reveal that audit committee expertise, auditor reputation, and profitability have an influence on audit report lag. In contrast, audit committee size, audit committee meetings, industry-specialist auditor, firm size, and solvency do not have effect on audit report lag.